INTEGRATION MODIFICATIONS OF THE ANALYTICAL HIERARCHY PROCESS FOR GROUP DECISION MAKING SUPPORT SYSTEMS - Mironova, N. A. (Radio Electronics, Computer Science, Control, 2012)
The systematization of Analytic Hierarchy Process existent modification is developed. The formalization of Analytic Hierarchy Process generalized approach for group decision making problems is solved.